AUGMENTATION OF FEMINIST DISCOURSE: REBELLION AGAINST PATRIARCHY IN ANITA NAIR’S MISTRESS - Richa; Singh, Pradeep (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Anita Nair's Mistress delves into the intricate interplay of patriarchy and how women in Indian society negotiate and eventually resist it. By portraying the characters and their journeys, Nair reveals the multifaceted system of power and societal expectations that influence the lives of women in modern-day India. The paper shall focus on how the female characters in the novel react against male domination and how characters in this novel shall be put under a certain frame of rebellious women to examine them critically and to understand the author’s message in creation of these types of characters. This study examines the novel to dissect how the female leads confront and oppose patriarchy through their decisions, actions, and interpersonal connections, shining a spotlight on women's strength and self-determination when confronted with societal limitations.